Design and optimization of a microwave irradiated and resonant continuous biochemical reactor. Issue 7 (30th July 2016) - Fanti, A.; Casu, S.; Desogus, F.; Djuric, N.; Mazzarella, G.
Abstract: The design of a microwave irradiated enzyme (biochemical) reactor is here presented. It consists of a suitable higher‐order mode resonant cavity which contains several tubes where the solution containing reagents and products flow in the laminar flow regime. The process evolution under irradiation has then been simulated using the COMSOL multiphysics environment. As an example, the enzymatic hydrolysis reaction of sucrose has been considered. The results of the multiphysics simulation show that such a reactor can be used to effectively perform the reaction process in the optimal conditions for maximizing the reaction rate and preventing the enzyme deactivation by a precise knowledge of the temperature distribution and its strict control. Key Points: An effective MW cavity to be used as an enzyme reactor has been designed and optimized The working cavity was simulated by a multiphysics approach and showed to be effective for the aim